Moricsalas vēsturiskā izkārtne - Jamonte, Daiga (My University, 2022)
Atzīmējot Moricsalas dabas rezervāta dibināšanas 110 gadadienu, Latvijas Universitātes Muzejs par mēneša priekšmetu izvēlējās rezervāta vēsturisko izkārtni. Rakstā sniegta informācija par rezervāta tapšanu un muzeja krājuma priekšmetiem, kas ir rezervāta pastāvēšanas pirmajām desmitgadēm.

Celebrating the 110th anniversary of the establishment of the Moritz Island Nature Reserve, the Museum of the University of Latvia chose the historical sign of the reserve as the object of the month. The article provides information about the establishment of the reserve and the objects of the museum collection, which are from the first decades of the existence of the reserve.
Moritz Island Historical Sign
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::NATURAL SCIENCES::Biology; Moricsalas dabas rezervāts; dabas aizsardzība; Rīgas Dabaspētnieku biedrība; Naturforscher-Verein zu Riga; Karl Reinhold Kupffer; Moritz Island; Nature Protection; Latvijas Universitātes Muzejs; the Museum of the University of Latvia